Modal Vibration Characteristic Analysis of Crank Shaft of the High-precision RV Reducer under Meshing State - Xingdong Xiao; Dongyi Hu; Guoping Li; Limin Luo; Linhuan Gong; Junqiang Lou (Jixie chuandong)
The transmission characteristics of the precision RV reducer is mainly determined by the mesh state of planetary gears and input gear shaft，and vibration modal characteristics of the crank shaft have important effects on the dynamic behavior of the RV reducer. Taking the RV-80E as an example，based on the 3D model of the first-stage reducer，the vibration modal characteristics of the crank shaft considering three states，namely the free，bearing support and mesh state，are obtained using the finite element analysis method. Through the simulation analysis， induced by the meshing gear series，the two eccentric shaft edges and the head deformation of the crank shaft considering the mesh state is the biggest，better with the working mode of the RV reducer than the other states，and the natural frequencies of the crank shaft increase remarkably. The research results provide a theoretical basis for optimization design of dynamic characteristics and meshing characteristics of crank shaft in first-stage reducer part.